2021
DOI: 10.3389/fimmu.2021.794099
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Immune-Related Adverse Events and Prognosis in Hepatocellular Carcinoma Patients Treated With Immune Checkpoint Inhibitors

Abstract: BackgroundImmune-related adverse events (irAEs) caused by immune checkpoint inhibitors (ICIs) were associated with clinical benefit in cancer patients of melanoma, a lung cancer. In the present study, we investigated the correlation between irAE and ICI efficacy in hepatocellular carcinoma (HCC) patients.MethodsWe divided the HCC patients who received the anti-PD-1 antibody into two groups as irAE group and non-irAE group according to the National Cancer Institute Common Terminology Criteria for Adverse Events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 42 publications
2
35
2
Order By: Relevance
“…. Our previous study also found that irAEs can also serve as a marker of good prognosis in hepatocellular carcinoma (HCC) [17]. The results that the irAEs associated with better treatment e ciency including DCR, PFS and OS in AGC was consistent with previous reports.…”
Section: Toxicitysupporting
confidence: 90%
“…. Our previous study also found that irAEs can also serve as a marker of good prognosis in hepatocellular carcinoma (HCC) [17]. The results that the irAEs associated with better treatment e ciency including DCR, PFS and OS in AGC was consistent with previous reports.…”
Section: Toxicitysupporting
confidence: 90%
“… 9 , 10 Interestingly, the development of irAEs was associated with better clinical outcome for HCC patients who were treated with ICIs, although the sample size was small. 16 Corticosteroid therapy is often indicated in the management of cancer-related symptoms such as cachexia, anorexia, edema in the central nervous system, or pain and is recommended by guidelines as first-line therapy for most irAEs. 17 , 18 Recently, Pinato et al reported that there is inadequate evidence about corticosteroid therapy before or during ICI therapy being associated with overall survival and progression-free survival in patients with HCC even at a dose of more than 10 mg/day.…”
Section: Discussionmentioning
confidence: 99%
“…All statistical analyses were performed using SPSS (IBM SPSS 20.0, NY, USA). All P values are two-sided, and p < 0.05 was considered to indicate a statistically significant difference [ 16 ].…”
Section: Methodsmentioning
confidence: 99%